1955
DOI: 10.1287/mnsc.1.3-4.233
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Certain Communication Nets Upon Organization and Performance in Task-Oriented Groups

Abstract: Bavelas, Smith and Leavitt (Bavelas, A. 1950. Communication patterns in task-oriented groups. J. Acoustical Soc. Amer. 22 725-730.) have posed the problem: what effect do communication patterns have upon the operation of groups? To study this problem they designed a laboratory situation that is a prototype of those occurring in "natural" organizations existing in government and business. Each member of the group is given certain information. Their task is to assemble this information, use it to make a decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
0
3

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(108 citation statements)
references
References 3 publications
3
102
0
3
Order By: Relevance
“…10 In the Weber and Camerer experiments firms took an average of 249 seconds (of communication) to complete the first period of the task and 48 seconds to complete the 20 th period. 11 Our experiments are therefore similar to an earlier line of research that investigated how the structure of an organization's "communication net" affects its ability to perform routines (Bavelas 1950, Bavelas and Barrett 1951, Carzo, Jr. and Yanouzas 1969, Christie et al 1956, Guetzkow and Simon 1955, Leavitt 1951, 1962, Shaw 1954. However, unlike this earlier research, varying whether the role of manager remains fixed or rotates in our experiment produces no change in how the laboratory task is performed in any period -one participant always performs the task as manager while the others serve as employees.…”
supporting
confidence: 72%
“…10 In the Weber and Camerer experiments firms took an average of 249 seconds (of communication) to complete the first period of the task and 48 seconds to complete the 20 th period. 11 Our experiments are therefore similar to an earlier line of research that investigated how the structure of an organization's "communication net" affects its ability to perform routines (Bavelas 1950, Bavelas and Barrett 1951, Carzo, Jr. and Yanouzas 1969, Christie et al 1956, Guetzkow and Simon 1955, Leavitt 1951, 1962, Shaw 1954. However, unlike this earlier research, varying whether the role of manager remains fixed or rotates in our experiment produces no change in how the laboratory task is performed in any period -one participant always performs the task as manager while the others serve as employees.…”
supporting
confidence: 72%
“…In similar experiments, Guetzkow and Simon (1955) subsequently showed that the star graph all but guarantees that at least one 'central' person receives all the information available in the network, which she or he can then disseminate to the rest of the organization members. Shaw (1954) went on to argue that "complex" (meaning more difficult) problems were better solved in "decentralized structures" (clusters), but Mulder (1960) later established that ultimately centralized (unclustered) networks performed better for both 6 simple and difficult problems, once a centralized and coordinated decision structure evolves within the experimentally imposed communication structure.…”
Section: Searching Information Spaces: Clustering Aids Performance?mentioning
confidence: 96%
“…Communication can also be enhanced by the type or 'shape' of the network: in a classic social psychology experiment, Leavitt (1951) found a 'wheel' arrangement, with communication being focussed through a central spokesperson, was the most efficient set-up, and made the least errors. However, group differences disappear if they are allowed enough time to organise themselves (Guetzkow & Simon, 1955) into a self-selected structure best suited to the problem.…”
Section: Expected Communication Outcomesmentioning
confidence: 99%